Potentiometric Sensor for Gadolinium(III) Ion Based on Zirconium(IV) Tungstophosphate as an Electroactive Material - Harish K. Sharma; Nadeem Sharma (E-Journal of Chemistry)
A new inorganic ion exchanger has been synthesized namely Zirconium(IV) tungstophosphate [ZrWP]. The synthesized exchanger was characterized using ion exchange capacity and distribution coefficient (Kd). For further studies, exchanger with 0.35 meq/g ion-exchange capacity was selected. Electrochemical studies were carried out on the ion exchange membranes using epoxy resin as a binder. In case of ZrWP, the membrane having the composition; Zirconium(IV) tugstophosphate (40%) and epoxy resin (60%) exhibits best performance. The membrane works well over a wide range of concentration from 1×10-5 to 1×10-1 M of Gd(III) ion with an over- Nernstian slope of 30 mv/ decade. The response time of the sensor is 15 seconds. For this membrane, effect of internal solution has been studied and the electrode was successfully used in partially non-aqueous media too. Fixed interference method and matched potential method has been used for determining selectivity coefficient with respect to alkali, alkaline earth, some transition and rare earth metal ions that are normally present along with Gd(III) in its ores. The electrode can be used in the pH range 4.0-10.0 for 10-1 M and 3.0-7.0 for 10-2 M concentration of target ion. These sensors have been used as indicator electrodes in the potentiometric titration of Gd(III) ion against EDTA and oxalic acid.